Understanding The Risk Factor of CTEV and Its Management at Primary Health Care - Arnadi Zubir; Muhammad Wiranata; Ihdina Zahra; Fahrul Rozy; Wahyuning Lestari; Achmad Fikri (Fakultas Kedokteran Universitas Riau, 2026)
Congenital Talipes Equinovarus (CTEV) is a congenital deformity affecting the lower extremities. CTEV is classified into four components: Cavus, Adductus, Varus, and Equinus. Risk factors for CTEV are most commonly associated with twin pregnancies, with a higher incidence reported in monozygotic twins compared to dizygotic twins (32% vs. 2.9%). Other contributing factors include maternal smoking during pregnancy, which has been reported to increase the risk of CTEV by approximately 1.3–2 times. In addition, exposure to teratogenic drugs during pregnancy may disrupt fetal musculoskeletal and neuromuscular development, increasing the risk of CTEV by 1.5–3 times, particularly during the first trimester, thereby increasing the likelihood of congenital deformities of the lower extremities. The Ponsetti method has a high success rate, is minimally invasive, and is effective in improving foot function and deformity when performed early in suspected CTEV patients. A 12-month-old twin infant presented to the outpatient clinic with deformities in both lower extremities. History taking revealed oligohydramnios, tobacco exposure, and medication consumption during pregnancy. Management was performed using the Ponseti method, including serial casting correction and bracing with Dennis Brown splint shoes which implemented in primary health care. Early recognition of risk factors may reduce the risk and severity of CTEV.